1982
DOI: 10.1097/00000658-198208000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Results of Ilioinguinal Dissection for Stage II Melanoma

Abstract: Eighty-two Stage II melanoma patients with inguinal lymph node metastases have undergone ilioinguinal node dissections at UCLA during the past 10 years. Twenty-four (29.3%) patients had involvement of both inguinal and iliac nodes, whereas 58 (70.7%) patients had only inguinal metastases. The frequency of iliac metastases did not relate to location, Clark's level or thickness of the primary tumor or interval from diagnosis of primary tumor to lymphadenectomy, but was related to the number of inguinal nodes inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 4 publications
2
21
0
Order By: Relevance
“…The incidence of iliac node tumor positivity is also directly related to the number of pathologically tumorpositive inguinal nodes. Finck et al 7 have shown that the incidence of tumor-positive iliac nodes increases from 14% when 1 inguinal node is pathologically tumor positive to 50% when 4 or more nodes are involved. Other investigators 32 have shown a 100% incidence of iliac node tumor positivity when 3 or more inguinal nodes contain metastatic disease.…”
Section: 421mentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of iliac node tumor positivity is also directly related to the number of pathologically tumorpositive inguinal nodes. Finck et al 7 have shown that the incidence of tumor-positive iliac nodes increases from 14% when 1 inguinal node is pathologically tumor positive to 50% when 4 or more nodes are involved. Other investigators 32 have shown a 100% incidence of iliac node tumor positivity when 3 or more inguinal nodes contain metastatic disease.…”
Section: 421mentioning
confidence: 99%
“…Other investigators [7][8][9][10][11] have demonstrated a survival benefit for subgroups of patients undergoing ILND and believe that ILND is a superior procedure to superficial groin dissection (SGD).…”
mentioning
confidence: 99%
“…This has prompted some to argue that the iliac nodal basin does not need to be approached unless Cloquet's node is involved with metastatic disease, and therefore, Cloquet's node essentially functions as an SLN for the iliac basin. Other predictors of iliac nodal involvement and need for complete dissection include four or more superficial groin nodes involved with disease [23,24].…”
Section: Melanomamentioning
confidence: 99%
“…2 of these patients died soon after operation and only 1 survived for 2.5 years and died with generalized melanoma. The massive extension of disease to the regional lymph nodes has been long recognized as an omnious sign of melanoma [7] and only an occassional patient with positive deep groin nodes will survive on a long-term basis after superficial and deep groin dissection [8]. Reports of patients with massive groin nodes from melanoma cured by hemipelvectomy are not known to us.…”
Section: Discussionmentioning
confidence: 99%